2014
DOI: 10.7752/jpes.2014.04079
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:An International Health, Racquet and Sportsclub Association's report (2013) recently referred to Cyprus as an emerging market in the fitness industry. Although Cypriot fitness agencies appear to be a growing business that both demands the acquisition of new members and, most importantly, the upkeep of the existing ones, not such research seems to have ever taken place in the country. This study's aim was to examine the patterns of service quality and satisfaction that may be used as safe predictors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…In 2019, nearly 12,000 collaborators were working as fitness professionals in Portugal (AGAP, 2020). Fitness professionals' importance for the satisfaction and retention of clients has been reported in several studies to be essential for the growth of the sector (Papadimitriou and Karteroliotis, 2000;Murray and Howat, 2002;Makover, 2003;Theodorakis et al, 2004;Tsitskari et al, 2014;Campos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, nearly 12,000 collaborators were working as fitness professionals in Portugal (AGAP, 2020). Fitness professionals' importance for the satisfaction and retention of clients has been reported in several studies to be essential for the growth of the sector (Papadimitriou and Karteroliotis, 2000;Murray and Howat, 2002;Makover, 2003;Theodorakis et al, 2004;Tsitskari et al, 2014;Campos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dada a importância da qualidade do serviço na satisfação do cliente, a literatura procura examinar a importância de diferentes determinantes desta qualidade. No contexto dos ginásios os investigadores destacam como determinantes os aspetos do envolvimento físico, como a qualidade do equipamento (Ferreira ou o ambiente acolhedor das instalações e das aulas (Tsitskari et al, 2014), as relações interpessoais do cliente-funcionário (Loureiro et al, 2019) e a tecnologia (Ferreira Barbosa et al, 2021).…”
Section: Metodologíaunclassified
“…Several studies have established a positive relationship between service quality and customer satisfaction in sports and fitness settings (Alexandris et al, 2004;Dias et al, 2019;Nuviala et al, 2012;Tsitskari et al, 2014;Yu et al, 2014). Physical infrastructure has the most significant impact on satisfaction in Lentell's (2000) study, while Papadimitriou and Karteroliotis (2000) showed that the quality of instructors has the most significant contribution, followed by the facility attraction and operation, the availability of the programmes and the way it was delivered.…”
Section: Service Quality Dimensions As Predictors Of Customer Satisfa...mentioning
confidence: 99%